Media Pembelajaran Anak Usia Dini dan Siswa Sekolah Dasar Berbasis Macromedia Flash 8 - Dita Anggi Purbasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
The development of games increases very fast. It can be seen by there are many kind of games. Here, the writer would like to create a game which is interesting and able to improve the way to love animals. The players are demanded to solve problems in each stage of game. Game status, instructions, and tools are provided by a game will guide players actively to look for information which are able to enrich their knowledge and strategy to play. To create a game, the writer needs Macromedia Flash 8. There are 12 kinds of main Sprite in this game and 3 rooms. To continue into the next level, the player should pass at the previous level. This game belongs to Action Platformer 2D which aims as the bridge to educate children. The game in level 1 spends around 1 minute, in level 2 is around 2-3 minutes, in level 3 is around 3-5 minutes. This game has passed testing step which was done at Windows 8.1 Enterprise 32 bit and Windows 10 Enterprise 64 bit.